Acute pediatric tracheitis: Distinguishing the disease by tracheostomy status. (March 2020) - Ni, Jonathan S.; Kohn, Jocelyn; Shah, Udayan K.; Levi, Jessica R.
Abstract: Objectives: Tracheitis is an upper airway infection that often presents in patients with tracheostomies and can potentially cause airway obstruction. This study aims to use a nationwide database to identify a large cohort of pediatric patients admitted with tracheitis to elucidate the management and resource utilization associated with the disease both with and without tracheostomies. Methods: The Kids' Inpatient Database (KID) 2012 was used to identify 2394 weighted discharges with acute tracheitis, with or without obstruction, as the primary diagnosis. Data on prior tracheostomy status, demographics, hospital characteristics, management, and resource utilization were obtained. Two groups of interest, based on presence of prior tracheostomy, were studied. Linear regression was performed to determine independent predictors of total charges. Results: The mean age was 5.52 years (SD: 5.54), mean length of stay (LOS) was 6.37 days (SD: 10.18), and mean total charges were $60, 996.61 (SD: 107, 798.41). Patients with prior tracheostomy had lower rates of endoscopy and endotracheal intubation than patients without ( p  < 0.0005). There was no significant difference in LOS ( p  = 0.076) or total charges ( p  = 0.210) between the groups based on prior tracheostomy status. Conclusion: Pediatric tracheitis should be differentiated on the basis of tracheostomy status. We propose that tracheitis diagnosis codes should be distinguished by the presence of tracheostomy as "open" and the absence of tracheostomy as "closed."